Clustering of Five Sweet Tamarind Based on Fruit Characteristic - Fitriana Nasution; Chinawat Yapwattanaphun (AGRIVITA, Journal of Agricultural Science, 2017)
Morphological and genetic characterization of tamarind are useful and important for breeding, commercialization and gene bank management. The cultivars characterized in this study were Intapalum, Sritong, Prakaitong, Khantee and Srichompoo. The comparison of five sweet tamarind cultivars were carried out using ANOVA and DMRT with 0.05 of significant levels. The relationship between morphological characteristics was calculated by the Pearson’s correlation coefficient. Phylogenetic analysis used NTSYSpc ver. 2.1 to generate a dendrogram of fruit characters. The quantitative characters (pod weight, pod diameter, and pod length) were significantly different. The biggest fruit was Sritong and the smallest was Khantee. Significant differences were shown on two qualitative characters such as pod shape and flesh color, while there were no significant difference on the seed shape, seed color and skin color. There were positive correlations among all quantitative pod characters of the samples. Pod weight was significantly correlated with pod diameter, however pod length and pod diameter were not significantly correlated. The similarity level from five sweet tamarind cultivars was 44-100 %.